3-Hydroxyisobutyryl-CoA hydrolase involved in isoleucine catabolism regulates triacylglycerol accumulation in Phaeodactylum tricornutum. (5th September 2017) - Pan, Yufang; Yang, Juan; Gong, Yangmin; Li, Xiaolong; Hu, Hanhua
Abstract : Since methylmalonyl-CoA epimerase appears to be absent in the majority of photosynthetic organisms, including diatoms, (S)-methylmalonyl-CoA, the intermediate of isoleucine (Ile) catabolism, cannot be metabolized to (R)-methylmalonyl-CoA then to succinyl-CoA. In this study, propionyl-CoA carboxylase ( PCC ) RNAi silenced strains and 3-hydroxyisobutyryl-CoA hydrolase ( HIBCH ) overexpression strains were constructed to elucidate the Ile degradation pathway and its influence on lipid accumulation in Phaeodactylum tricornutum based on growth, neutral lipid content and metabolite profile analysis. Knockdown of PCC disturbed the metabolism of Ile through propionyl-CoA to methylmalonyl-CoA, as illustrated by much higher Ile content at day 6. However, Ile decreased to comparable levels to the wild-type at day 10. PCC silencing redirected propionyl-CoA to acetyl-CoA via a modified β-oxidation pathway, and transcript levels for some branched-chain amino acid (BCAA) degradation-related genes, especially HIBCH, significantly upregulated in the PCC mutant, which enhanced the BCAA degradations and thus resulted in higher triacylglycerol (TAG) content. Overexpression of HIBCH accelerates Ile degradation and results in a lowered Ile content in the overexpression strains, thus enhancing carbon skeletons to the tricarboxylic acid cycle and giving rise to increasing TAG accumulation. Our study provides a good strategy to obtain high-lipid-yield transgenic diatoms by modifying the propionyl-CoA metabolism. This article is part of the themed issue 'The peculiar carbon metabolism in diatoms'.